Monoamine neurotransmitters in breast cancer: Progression, immunomodulation, and therapeutic strategies - Saeed Mahdianipur; Mahafarin Maralani; Homa Davoodi (Jorjani Biomedicine Journal)
Monoamine neurotransmitters, including serotonin, dopamine, histamine, and adrenaline/noradrenaline (epinephrine/norepinephrine), are key neuromodulators in the nervous system that influence complex behavioral and cognitive functions. They also affect peripheral tissues and inflammation, playing a crucial role in the biology of various malignancies, including breast cancer, the most common cancer among women worldwide. These neurotransmitters are essential for mammary gland development and are linked to depression, a major breast cancer risk factor. Elevated levels of circulating proinflammatory cytokines in depression may mediate neuroendocrine, neural, and immune pathways, affecting the metabolism of monoamine neurotransmitters. In the tumor microenvironment, serotonin and norepinephrine generally exhibit pro-tumorigenic effects, while dopamine has shown promising anti-tumor activity by enhancing immune responses. Histamine also shows potential in anti-tumor immunity, although its effects on breast cancer progression remain inconclusive. Research into the relationship between these neurotransmitters and breast cancer cell growth highlights their significant role in breast cancer biology and their potential in improving treatment outcomes. This review explores the role of monoamine neurotransmitters in breast cancer progression, their immunomodulatory functions, and the therapeutic potential of targeting these neurotransmitters. By analyzing these complex relationships, we aim to illuminate novel therapeutic strategies that could enhance the clinical management of breast cancer.